Pengaruh Reward dan Punishment terhadap Kinerja Karyawan pada Bank Syariah Indonesia KCP Medan Pulo Brayan - Nuzul Ramadhan; Muhammad Ridwan; M. Ikhsan Harahap (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This research aims to determine the effect of rewards and punishment on employee performance at PT. Indonesian Sharia Bank KCP Medan Pulo Brayan. The research method used is an associative quantitative method. And the sample in this study used saturated sampling, namely 32 people. The data collection instrument uses a questionnaire which is tested for validity, normality and reliability. The dependent variable is the employee performance variable and the independent variables are Reward and Punishment. Data analysis techniques use multiple linear regression, hypothesis testing, t-test, F-test and coefficient of determination. The results of the t test show that Reward (X₁) has a significant effect on employee performance (Y) at Bank Syariah Indonesia KCP Medan Pulo Brayan with tcount (3.609) > ttable (2.04523). Punishment (X2) has a significant effect on employee performance (Y) at Bank Syariah Indonesia KCP Medan Pulo Brayan with t count (4.286) > t table (2.04523). And there is a significant influence of Reward and Punishment together on PT Employee Performance. Bank Syariah Indonesia KCP Medan Pulo Brayan with Fcount (110.061) > Ftable (3.33) and Sig value < 0.05 (0.000 < 0.05). The coefficient of determination (R) value is 0.876 or 87.6%. This means that the Employee Performance variable can be explained by the Reward and Punishment variables.